The Influence of Motivation and Work Discipline on Employee Performance at the Regional Development Planning, Research and Innovation Agency (Bapperida) of Bulukumba Regency - Muhammad Fadil Harfa; Sitti Nurbaya; Zalkha Soraya (Pustaka Digital Indonesia, 2025)
The urgency of this research lies in the importance of improving employee performance as a key factor in the success of regional development planning and implementation at BAPPERIDA Bulukumba Regency. Given the indications of declining performance in recent years, this study is relevant for identifying internal factors such as motivation and work discipline that can be promptly addressed by management. The aim of this research is to find out whether motivation and work discipline variables influence employee performance at the Regional Development Planning, Research and Innovation Agency Bulukumba Regency. The type of research carried out is quantitative research. The population in this study were all employees at the Regional Development Planning, Research and Innovation Agency Bulukumba Regency, totaling 74 employees consisting of 44 ASN and 30 non-ASN. The sampling technique used in this research was saturated sampling. Therefore, the number of samples in this research was 74 employees. The criteria for this sample are employees consisting of 44 ASN and 30 non-ASN. The type of data used in this research is quantitative data obtained from distributed questionnaires and is related to the problem being studied. Data collection was carried out by distributing questionnaires and documentation. In this research, the data sources used in data collection include primary data. Based on the results of research using statistical calculations through the Statistical Package for the Social Science version 26 (SPSS26) application, the results show that motivation and work discipline variables partially have a positive and significant effect on employee performance at the Regional Development Planning, Research and Innovation Agency Bulukumba Regency.